Use of character-based abc lima dasar educational games for 3-5 year olds in Raudhatul Athfal - Primanisa, Reiska (Al-Athfaal: Jurnal Ilmiah Pendidikan Anak Usia Dini, 2025)
Background: Early childhood education institutions are required to provide learning media that effectively stimulate cognitive development and character formation in children aged 3–5 years. Play-based educational games are considered highly relevant during the golden age of development; however, learning media in many Raudhatul Athfal remain limited and insufficiently optimized. Objective: This study aims to analyze research trends related to the Character-Based Five Basic ABC Educational Game in supporting early childhood learning. Method: A qualitative bibliometric method was employed using Publish or Perish (PoP) and VOSviewer software. Data were collected from 100 journal articles indexed in Google Scholar and Sinta published between 2019 and 2024. The analysis focused on publication trends, productive institutions, citation frequency, publishers, and keyword co-occurrence mapping. Results: The findings show a consistent increase in publications over the last five years, forming six major research clusters. Bibliometric visualization indicates that the keywords “game,” “character,” and “child” have the highest link strength, reflecting strong integration between cognitive skills and character education. Conclusion: The Character-Based Five Basic ABC Educational Game is identified as a relevant and innovative learning medium that supports both cognitive and character development in early childhood education.